Monitoring Tritrophic Biocontrol Interactions Between Bacillus spp., Fusarium oxysporum f. sp. cubense, Tropical Race 4, and Banana Plants in vivo Based on Fluorescent Transformation System - He, Ping; Li, Shu; Xu, Shengtao; Fan, Huacai; Wang, Yongfen; Zhou, Wei; Fu, Gang; Han, Guangyu; Wang, Yun-Yue; Zheng, Si-Jun (Frontiers in Microbiology, 2021)
Bacillus spp. is effective biocontrol agents for Fusarium wilt of banana (FWB), tropical race 4 (TR4). This study explores the colonization by Bacillus subtilis, Bacillus velezensis, and Bacillus amyloliquefaciens of host banana plants and elucidates the mechanism of antagonistic TR4 biocontrol. The authors selected one B. subtilis strain, three B. velezensis strains, and three B. amyloliquefaciens strains that are proven to significantly inhibit TR4 in vitro, optimized the genetic transformation conditions and explored their colonization process in banana plants. The results showed that we successfully constructed an optimized fluorescent electro-transformation system (OD600 of bacteria concentration=0.7, plasmid concentration=50ng/μl, plasmid volume=2μl, transformation voltage=1.8kV, and transformation capacitance=400Ω) of TR4-inhibitory Bacillus spp. strains. The red fluorescent protein (RFP)-labeled strains were shown to have high stability with a plasmid-retention frequency above 98%, where bacterial growth rates and TR4 inhibition are unaffected by fluorescent plasmid insertion. In vivo colonizing observation by Laser Scanning Confocal Microscopy (LSCM) and Scanning Electron Microscopy (SEM) showed that Bacillus spp. can colonize the internal cells of banana plantlets roots. Further, fluorescent observation by LSCM showed these RFP-labeled bacteria exhibit chemotaxis (chemotaxis ratio was 1.85±0.04) toward green fluorescent protein (GFP)-labeled TR4 hyphae in banana plants. We conclude that B. subtilis, B. velezensis, and B. amyloliquefaciens can successfully colonize banana plants and interact with TR4. Monitoring its dynamic interaction with TR4 and its biocontrol mechanism is under further study.